Local Wisdom of Baduy Community: Systematic Literature Review on Social, Cultural, and Environmental Ethics - Damanhuri Damanhuri; Aceng Hasani; Ujang Jamaludin (Jurnal Moral Kemasyarakatan, 2025)
The indigenous knowledge of the Baduy people encompasses social, cultural, and environmental elements essential for sustainable development. This study intends to examine and integrate literature about social, cultural, and environmental ethics within Baduy wisdom. The employed methodology is a systematic literature review adhering to the PRISMA 2020 principles. A literature search was performed via Google Scholar and Scopus via the Publish or Perish tool, encompassing papers from 2016 to 2024, along by a comprehensive analysis of 8 chosen articles. The study's findings delineate three primary themes: social ethics (pertaining to customary structures and community organisations), cultural ethics (concerning the significance of rituals and spiritual values), and environmental ethics (focused on nature conservation and restrictions on environmental alteration) through customary law (Pikukuh), spiritual beliefs (Sunda Wiwitan), traditional agricultural practices, and intergenerational oral traditions (Pamali). This study reinforces the concept of a comprehensive and community-oriented framework for sustainable living, grounded in the ideals of simplicity, collaboration, and harmony with nature. Notwithstanding the variety of existing research, considerable deficiencies persist, particularly in the analysis of social, cultural, and environmental ethics rooted in local wisdom, the interdisciplinary comprehension of the Baduy community's knowledge system, and the imperative of integrating local wisdom into global dialogues on sustainability and cultural preservation.